THE DIFFICULTIES OF STUDENTS TO WRITE NARRATIVE TEXT AT THE EIGHTH GRADE STUDENTS OF SMP NEGERI 1 LOLOWAU - M. Yunus Laia (Jurnal Education and Development, 2019)
The objective of this research is to expalain the kinds and the reasons of difficulties in writing narrative text which was devided into grammar,vocabulary,speeling, handwriting, punctuation and layout done by the eighth grade students of SMP Negeri 1 Lolowau especially in writing narrative text. In doing this study, the writer used descriptive analysis of qualitative research design. Additionally, in collecting the data document and interview were used. English teacher and students were interviewed to get additional information about the background of students’ knowledge in writing narrative text, and test was given to the students to know the difficulties they made. Furthermore, the participants of the test were 20 of the eighth grade students of SMP Negeri 1 Lolowau. Both result of interview and test were analyzed to get a comprehensive conclusion. The finding shows that most of students got difficulties in writing narrative text. The classification of difficulties which has been done by the students is grammar, vocabulary, speeling, punctuation and layout and layout except, in handwriting. The result of interview shows that the reasons of difficulties during writing narrative text faced by students were students have not enough knowledge about English structure, lack of vocabulary, students are not interested in learning English or students lack of motivation,the first language influences the learners’ concept about English pattern and the way of reading and writing are different. Knowing the diffuculties and causes of them, it is suggested to English teacher at this school to overcome the difficulties of students to write narrative text.